Bases del sistema inmune de la abeja melífera (Apis mellifera): Revisión - Larsen, Alejandra Edith (2019)
Honey bees (Apis mellifera) pollinate plants in both natural and managed ecosystems, contributing to food production and sustaining and increasing biodiversity. Unfortunately bee depopulation and colony losses are becoming increasingly common worldwide. Several factors contribute to the decline of bee populations, including pathogens (parasites, fungi, bacteria and viruses), ecosystem alteration or loss, and/or agrochemical use. All of these factors alter the defense mechanisms of the bee immune system. Honey bees have an innate immune system that includes physical barriers and generalized cellular and humoral responses to defend themselves against infectious and parasitic organisms. Pathogens, acaricides, fungicides, herbicides and other pesticides affect the bee immune system and consequently bee health. The defense mechanisms of the bee immune system include signaling pathways, pathogen recognition receptors and innate immune system effectors. Although A. mellifera’s immune system is very similar to that of Drosophila flies and Anopheles mosquitoes, they possess only about a third of the immune system genes identified in these genera. This relatively low number of genes is probably a consequence that A. mellifera has developed social immunity. This defense strategy lowers pressure on the individual immune system of bees. This review article summarizes and discusses the bases of the honey bee immune system.